KNOWLEDGE AND ACTIVITY OF COMMUNITY HEALTH WORKERS REGARDING HYPERTENSION AND ITS MANAGEMENT IN MALANG - Mifetika Lukitasari; Dwi Adi Nugroho; Budi Satrijo; Mohammad Saifur Rohman; Cholid Tri Tjahjono (Journal of Nursing Science Update (JNSU), 2019)
Community health workers have had an increasing role in CVD prevention and control. Their knowledge and activity contributed to hypertension management in community. Hence, this study aimed to assess the knowledge of community health workers in community. This cross sectional study was conducted in 94 community health workers. All of the participants worked in primary geriatric community health service (posyandu lansia). Hypertension knowledge and management activity in the community was assessed by questionnaire. Most of the community health workers (57%) had high knowledge level. Participants with high knowledge had significant awareness of hypertension and higher knowledge on hypertension therapy, medication adherence, life style, diet, and hypertension complication compared to those of low knowledge level. Moreover, both groups had similar activities in community regarding hypertension management, such as blood pressure measurement, health education, and body mass index measurement. This study suggested that all health care workers shared similar activity in community hypertension management regardless their knowledge level.